ISLAMIC GUIDANCE AND COUNSELING: ISLAMIC SCIENCE POINT VIEW - Nurhasanah, Rizki (Al-Amien Prenduan University, Sumenep, 2022)
Islamization is an effort to maintain and preserve the teachings of Islam that have been brought by the Prophet Muhammad, as well as efforts to liberate Muslims from underdevelopment in many sectors of life. One of them is the development of science. Guidance and Counseling as a science that is in direct contact with the community, of course, must receive more attention in its knowledge. It has been described in many previous studies about the study of counseling guidance that is not in accordance with Islamic teachings. So that in this study, we will examine in depth the history, definitions, principles, functions, and objectives of counseling guidance in the Islamization approach which was initiated by Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi. The purpose of this study is that prospective Islamic counselors have an overview and insight into the study of appropriate counseling guidance in Islamic teachings.